Gain time to adapt: How sorghum acquires tolerance to salinity - Abuslima, Eman; Kanbar, Adnan; Raorane, Manish L.; Eiche, Elisabeth; Junker, Björn H.; Hause, Bettina; Riemann, Michael; Nick, Peter (Frontiers in Plant Science, 2022)
Salinity is a global environmental threat to agricultural production and food security around the world. To delineate salt-induced damage from adaption events we analysed a pair of sorghum genotypes which are contrasting in their response to salt stress with respect to physiological, cellular, metabolomic, and transcriptional responses. We find that the salt-tolerant genotype Della can delay the transfer of sodium from the root to the shoot, more swiftly deploy accumulation of proline and antioxidants in the leaves and transfer more sucrose to the root as compared to its susceptible counterpart Razinieh. Instead Razinieh shows metabolic indicators for a higher extent photorespiration under salt stress. Following sodium accumulation by a fluorescent dye in the different regions of the root, we find that Della can sequester sodium in the vacuoles of the distal elongation zone. The timing of the adaptive responses in Della leaves indicates a rapid systemic signal from the roots that is travelling faster than sodium itself. We arrive at a model where resistance and susceptibility are mainly a matter of temporal patterns in signalling.